2005
DOI: 10.1089/jop.2005.21.400
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Olopatadine Hydrochloride 0.1% in the Treatment of Vernal Keratoconjunctivitis and Goblet Cell Density

Abstract: Olopatadine hydrochloride 0.1% is an effective agent for relieving the signs and symptoms of vernal keratoconjunctivitis. Also, it reduces the number of goblet cells, which, in turn, decreases the amount of mucus discharge in vernal keratoconjunctivitis during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 19 publications
0
32
0
2
Order By: Relevance
“…Olopatadine hydrochloride 0.1% e/d were used along with steroids in patients and proved beneficial for long term treatment. Corum et al reported that 2 months treatment with olopatadine hydrochloride 0.1% relieves the signs and symptoms of VKC 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Olopatadine hydrochloride 0.1% e/d were used along with steroids in patients and proved beneficial for long term treatment. Corum et al reported that 2 months treatment with olopatadine hydrochloride 0.1% relieves the signs and symptoms of VKC 10 .…”
Section: Discussionmentioning
confidence: 99%
“…However, both drugs were efficient and safe relieving the main symptoms and signs of VKC, including itching, tearing, conjunctival hyperemia, mucous discharge and photophobia. Olopatadine hydrochloride 0.1% was effective for relieving the signs and symptoms of VKC and reducing the number of goblet cells during treatment [30]. …”
Section: Management Of Vkcmentioning
confidence: 99%
“…Activated eosinophils are known to increase MUC5AC expression [43] and, therefore, could contribute to the mucus discharge observed in these patients. Following topical anti-allergic and anti-inflammatory treatments in VKC patients, there are reductions in conjunctival goblet cell number and MUC5AC expression towards normal levels [44,45]. …”
Section: Alteration Of Mucins In Ocular Surface Diseasementioning
confidence: 99%